2019
DOI: 10.15171/jlms.2019.17
|View full text |Cite
|
Sign up to set email alerts
|

Experience of 138 Transurethral Urethrotomy With Holmium:YAG Laser

Abstract: Introduction: Many valid option modalities are available for the management of urethral stricture disease (USD), such as internal urethrotomy which has the success rates of 33%–60%. The aim of this study was to assess the outcome of holmium: YAG (Ho: YAG) laser urethrotomy (HLU). Methods: One hundred thirty-eight patients with urethral stricture with the mean age of 48±3.03 years old treated by HLU from March 2011 to August 2017. The main purpose of this investigation was to evaluate mean operation time, stri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Karkan et al reported a 73.2% success rate with Holmium urethrotomy in their clinical experience with 138 patients (20). Evaluation of previous studies is shown in Table 4.…”
Section: Discussionmentioning
confidence: 99%
“…Karkan et al reported a 73.2% success rate with Holmium urethrotomy in their clinical experience with 138 patients (20). Evaluation of previous studies is shown in Table 4.…”
Section: Discussionmentioning
confidence: 99%
“…Today, the laser has an excellent application in urologic diseases. [22][23][24] Endoscopic laser lithotripsy (LL) is frequently used to manage patients with urolithiasis. 8,25 A number of lasers have been used for LL, of which the Ho:YAG has become one of the most frequently used one.…”
Section: Discussionmentioning
confidence: 99%
“…9 The Holmium laser has a good penetration depth, which helps in staunching blood; it is also used for other urologic surgeries, including urolithiasis, 10,11 bladder tumor, 6 genital skin lesion, 12 and urethrotomy. 13,14 The Holmium laser enucleation of the prostate (HoLEP) was introduced about 20 years ago as a surgical treatment for the lower urinary tract symptom (LUTS) resulting from BPH. 15 Despite some drawbacks such as a special equipment requirement and a steep learning curve, it seems that HoLEP is an efficient surgical approach to BPH.…”
Section: Introductionmentioning
confidence: 99%